Focal-onset seizure due to left internal carotid artery dissection in the context of confounding hyperglycaemia. Issue 3 (16th March 2022) - Moulder, Zachary; Kosela, Monika; Zafar, M Ahtsham; Jha, Abhinav; Gopal, Karthik; Pandey, Anmol
ABSTRACT: A 36-year-old diabetic woman presented to hospital with a seizure that started with shaking of the right hand which sequentially progressed to the entire right side of the body with associated loss of consciousness. Capillary Blood Glucose was 29 mmol/L. HbA1c was 133 mmol/L. Non-contrast computerised tomography (CT) scan of the brain was normal suggesting that the cause of her seizure was hyperglycaemia. However, Magnetic Resonance Imaging (MRI) of the brain showed infarcts in the left paracentral lobule and caudate nucleus. It also identified loss of signal flow void in the intracranial segment of the left internal carotid artery (ICA) raising the suspicion for thrombosis secondary to dissection. This was later confirmed on CT angiogram. This case demonstrates how the initial CT Head was non-diagnostic. We stress the importance of taking a careful seizure history and subsequently obtaining an MRI scan to fully exclude structural pathology.